Comparative performance of between-population vaccine allocation strategies with applications for emerging pandemics. Issue 11 (10th March 2023) - Joshi, Keya; Rumpler, Eva; Kennedy-Shaffer, Lee; Bosan, Rafia; Lipsitch, Marc
Highlights: Vaccine allocation between populations during emerging pandemics is challenging. Using a SEIR model, we compare the impact of various vaccine allocation strategies. We vary population size, risk structure, underlying immunity, and roll-out speed. We show that in most cases, allocation proportional to population size is optimal. Abstract: Vaccine allocation decisions during emerging pandemics have proven to be challenging due to competing ethical, practical, and political considerations. Complicating decision making, policy makers need to consider vaccine allocation strategies that balance needs both within and between populations. When vaccine stockpiles are limited, doses should be allocated in locations to maximize their impact. Using a susceptible-exposed-infectious-recovered (SEIR) model we examine optimal vaccine allocation decisions across two populations considering the impact of characteristics of the population (e.g., size, underlying immunity, heterogeneous risk structure, interaction), vaccine (e.g., vaccine efficacy), pathogen (e.g., transmissibility), and delivery (e.g., varying speed and timing of rollout). Across a wide range of characteristics considered, we find that vaccine allocation proportional to population size (i.e., pro-rata allocation) performs either better or comparably to nonproportional allocation strategies in minimizing the cumulative number of infections. These results may argue in favor of sharing of vaccines between locations in the context of an epidemic caused by an emerging pathogen, where many epidemiologic characteristics may not be known.